The experience of fatherhood: between challenges and possibilities - Leturiondo, Emanuelle Kist; de Souza, Bruno Pereira; Schmalfuss, Joice Moreira; Honnef, Fernanda; Tier, Cenir Gonçalves; Prates, Lisie Alende (Disciplinarum Scientia | Saúde, 2025)
Objective: to understand the meanings, challenges and possibilities for men in the experience of fatherhood. Methodology: qualitative research, developed between July and October 2021, with 10 parents. Semi-structured individual interviews were used, followed by thematic content analysis. Results: fatherhood was defined from the perspective of the man’s participation and responsibility for caring for his partner and child. Among the challenges, there was a restriction on health professionals regarding the presence of fathers in baby care, the hours of care and legislation, which impact their participation in this process. They suggest that health professionals encourage paternal inclusion and the development of educational strategies that allow greater instrumentalization for the development of maternal and child care. Conclusion: Men are breaking old paradigms of being the breadwinners of the home and establishing a new experience of fatherhood. Fathers need to be included to improve parental well-being and the bond with the baby. Educational strategies are needed to enable men to be better equipped to develop maternal and child care.